PENINGKATAN HASIL BELAJAR PENGUKURAN SUDUT MELALUI PENERAPAN METODE DEMONSTRASI PADA PESERTA DIDIK KELAS IV SD - Herlina Herlina (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study aims to see whether the application of the demonstration method improves the mathematics learning outcomes of angle material in fourth grade students of SD Negeri 01 Pasangkayu in the 2018/2019 academic year. The subjects of this study were educators and fourth grade students of SD Negeri 01 Pasangkayu, Pasangkayu District, Pasangkayu Regency which consisted of 23 students. This research is a Classroom Action Research (CAR) which consists of 2 cycles, each cycle is a series of activities, each of which consists of 4 stages, namely planning, implementation, observation, and reflection. This Classroom Action Research (CAR) uses data observation methods, namely written tests, sheets, and documentation. Data analysis was carried out by comparing the scores of each cycle with the KKM (Minimum Completeness Criteria) which was set at 75. Based on the results of this study, it was shown that the application of the demonstration method could improve the mathematics learning outcomes of angle measurement in fourth grade students of SD Negeri 01 Pasangkayu. This can be proven from the results of the pre-cycle before applying the demonstration method 17% of students who have completed, while there are still 83% of students who have not met the KKM. In the first cycle rose to 91% of students who completed. Then in the second cycle it rose to 100% of students who had completed their studies.